2017
DOI: 10.1177/1010428317728480
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and radiosensitizing synergistic effects of apigenin and cryptotanshinone against solid Ehrlich carcinoma in female mice

Abstract: Considerable attention has been paid to the introduction of novel naturally occurring plant-derived radiosensitizer compounds in order to augment the radiation efficacy and improve the treatment outcome of different tumors. This study was therefore undertaken to evaluate the antitumor, antiangiogeneic, and synergistic radiosensitizing effects of apigenin, a dietary flavonoid, and/or cryptotanshinone, a terpenoid isolated from the roots of Salvia miltiorrhiza, against the growth of solid Ehrlich carcinoma in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 69 publications
(88 reference statements)
0
26
0
Order By: Relevance
“…In order to grow Ehrlich solid tumor (EST) in the thigh, 0.2 mL EAC cells (2.5 × 106 cells/mouse) were subcutaneously inoculated at the right thigh of the lower female mouse limb. 5 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to grow Ehrlich solid tumor (EST) in the thigh, 0.2 mL EAC cells (2.5 × 106 cells/mouse) were subcutaneously inoculated at the right thigh of the lower female mouse limb. 5 …”
Section: Methodsmentioning
confidence: 99%
“…and metastasis, as well as angiogenesis, all of which are well-established cancer hallmarks. 5 Apoptosis is a cellular cycle, organized and coordinated, occurring under physiological and pathological conditions. It is the main event that regulates the occurrence and/or spread of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, apigenin alongside genistein and quercetin enhanced radiation-induced cell death by decreasing DNA damage renewal and cell repopulation, demonstrating higher antitumor activities [327]. Additional in vivo studies also demonstrated the radiosensitizing effects of apigenin in Ehrlich carcinoma-bearing mice exposed to whole body γ irradiation via the down-regulation of angiogenic regulators such as vascular endothelial growth factor-C (VEGF-C), down-regulation of matrix metalloproteinase-2 (MMP2), and the enhancement of apoptosis [328]. The radiosensitizing effects of quercetin have also been demonstrated in DLD-1 human colorectal cancer xenograft model in vivo and in HeLa and MCF-7 cells in vitro [329,330].…”
Section: Radiosensitizing Effects Of Cyp1b1 Inhibitorsmentioning
confidence: 99%
“…According to the model of granule-mediated apoptosis, killing involves degranulation and subsequent transfer of these proteases into the cytoplasm of the target cell, where they rapidly induce apoptosis [35]. This process is inhibited in cancer, which leads to the accumulation of various genetic unstable cells [36].…”
Section: Treatment Of Experimental Animals Bearing Ecmentioning
confidence: 99%